The wedge insole for the treatment of knee osteoarthritis: A systematic review protocol. Issue 37 (September 2019) - Chen, Shuling; Sun, Yicheng; Ma, Guanhua; Yin, Xunlu; Liang, Long
Abstract: Background: Functional limitations and pain are common presenting complaints for people suffering from knee osteoarthritis. Wedge insole can be sued for treatment of knee osteoarthritis. Hence, we conducted a systematic review and meta-analysis to explicit the efficacy of wedge insole in the treatment of knee osteoarthritis. Methods: A systematic literature search for studies will be performed in MEDLINE, Embase, the Chinese National Knowledge Infrastructure Database (CNKI), Cochrane Library, Web of Science. The methodological quality of the included studies using the risk bias assessment tool of Cochrane. Funnel plot will be used to assess the reporting bias. And the level of evidence for results are assessed by the GRADE method. Statistical analysis is conducted with Revman 5.3. Results: This systematic review and meta-analysis will provide a synthesis of evidences for wedge insole on knee osteoarthritis. Conclusion: The conclusion of this study will provide recommendations to assess effectiveness of exercise on knee osteoarthritis, which may further guide clinical practice. PROSPERO registration number: CRD42018096804